2021
DOI: 10.1097/pts.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Related Circumstances for Hospital Readmissions: A Case Series From 2 New York City Hospitals

Abstract: The aim of the study was to determine the main factors contributing to hospital readmissions and their potential preventability after a coronavirus disease 2019 (COVID-19) hospitalization at 2 New York City hospitals.Methods: This was a retrospective study at 2 affiliated New York City hospitals located in the Upper East Side and Lower Manhattan neighborhoods. We performed case reviews using the Hospital Medicine Reengineering Network framework to determine potentially preventable readmissions among patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…This finding was aligned with previous multicentric studies that reported readmission rates from 4.5 to 7%. 20 , 21 , 22 Our study highlighted that older individuals and those admitted with severe COVID-19 disease remain at risk of complications after discharge. The higher mortality and rehospitalization rates in the elderly could be due to a lower avidity in mounting a humoral response in those individuals.…”
Section: Discussionmentioning
confidence: 76%
“…This finding was aligned with previous multicentric studies that reported readmission rates from 4.5 to 7%. 20 , 21 , 22 Our study highlighted that older individuals and those admitted with severe COVID-19 disease remain at risk of complications after discharge. The higher mortality and rehospitalization rates in the elderly could be due to a lower avidity in mounting a humoral response in those individuals.…”
Section: Discussionmentioning
confidence: 76%
“…This contrasts with the results of a review of COVID-19 patients admitted to two hospitals in New York City in March–April 2020, where 56% of readmissions were due to dyspnea or hypoxia from COVID-19. 14 This may be related to differences in the index admission length of stay, which was 3 days in the New York City cohort vs. 8 days in our study, when the acute phase of COVID-19 is more likely to have resolved. Despite this discrepancy, the proportion of preventable readmissions in both studies were similar (17% vs. 25%).…”
Section: Discussionmentioning
confidence: 64%
“…While numerous studies have evaluated risk factors for readmission following hospitalization for COVID-19, few have systematically evaluated revisit preventability. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 An understanding of the factors contributing to preventable revisits specifically would allow for more targeted development and deployment of interventions that may help decrease future revisits. In this study, we employ the prior methodology developed by members of the Hospital Medicine Reengineering Network (HOMERuN) to evaluate the preventability of hospital revisits occurring within 30 days of hospital discharge of patients with COVID-19, including hospital readmissions and visits to the emergency department (ED) without admission.…”
mentioning
confidence: 99%
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%